Development of Integrated Waste Management Information System to Support Sustainable Development - Amali, Lanto Ningrayati; Padiku, Indhitya R.; Hunta, Aprilia M (Jambura Journal of Informatics, 2024)
The issue of waste in Indonesia is still a severe problem that has not been resolved, and Indonesia is included among the top 10 countries as the most significant waste producer. These problems include people throwing their consumption waste in the open or even burning it, the lack of systematization of integrated waste management to provide information on waste collection and transportation, which causes environmental pollution and hurts public health, and the lack of effective monitoring and reporting in waste management. This hampers practical evaluation, planning, and decision-making efforts in waste handling and in conducting a waste retribution or payment system by the community. This research aims to develop a web-based integrated waste management information system to support sustainable development. The system development method used is the prototype model through the stages of communication, quick planning, modeling, quick design, prototype construction, deployment delivery, and feedback. The result of this research is the availability of data and information on waste management effectively and efficiently; this system can perform adequate data collection and documentation in registering all units affiliated with waste management to record waste payment transactions. In addition, this system can assist in managing and supervising the entire waste management process efficiently.